Exploring regulatory roles of putrescine-doped zinc oxide nanoentities on ethylene signaling, redox imbalance, and programmed cell death in drought-stressed rice (Oryza sativa L.) seedlings - Das, Abir; Janda, Tibor; Sil, Sudipta Kumar; Adak, Malay Kumar (Frontiers in Plant Science, 2025)
We investigated the synergistic effects of putrescine-doped zinc oxide nanoparticles (PUT-nZnO) on drought-stressed rice seedlings. Our results demonstrate that PUT-nZnO enhances drought stress (DS) tolerance by improving redox balance, chloroplast integrity, and polyamine (PA) metabolism, offering a novel nano-biotechnological approach for crop resilience. Fourteen-day-old seedlings of rice (Oryza sativa L. cv. Swarna Sub1) were treated with PUT by foliar spray, singly and in combination with PUT-nZnO under 12% polyethylene glycol (PEG)-induced DS. Growth attributes, thermo-imaging, chloroplast ultrastructure, PA and ethylene signaling, relative cell death, redox metabolism, and nuclear lysis were the major parameters used to evaluate stress mitigation. DS initially caused a 48% decrease in relative water content, which was recovered to 126% under PUT-nZnO treatment. PUT-nZnO directly improved membrane integrity, reduced DNA loss, restored ion homeostasis via ATP hydrolysis, and supported cellular conformity and viability. These effects reduced DS-induced oxidative signaling through enhanced antioxidation. Oxidative stress under DS was mitigated, as indicated by a 41% reduction in H2O2 in the DS+PUT-nZnO treatment. Distribution of PAs and the activity of PA-oxidizing enzymes induced energy transfer within the chloroplast and reactive oxygen species (ROS) generation to activate enzymatic pathways. The mechanism for DS tolerance is indicated by nZnO through securing osmotic turgidity and mineral nutrient support, complemented synergistically by the antioxidation capacity of PUT. This study presents a promising biocompatible strategy for improving drought tolerance in rice during the early growth stage via the combined application of PUT and nZnO.